Factors Affecting the Weaning from Nasal CPAP in Preterm Neonates - Shantanu Rastogi; Hariprem Rajasekhar; Anju Gupta; Alok Bhutada; Deepa Rastogi; Jen-Tien Wung (International Journal of Pediatrics)
Objective. Identification of the weight and postmenstrual age (PMA) at successful weaning of NCPAP in preterm neonates and the factors influencing the successful wean. Study Design. Retrospective review of 454 neonates ≤32 weeks of gestational age (GA) who were placed on NCPAP and successfully weaned to room air was performed. Results. Neonates had a mean birth weight (BW) of 1357±392 grams with a mean GA of 29.3±2.2 weeks. Neonates were weaned off NCPAP at mean weight of 1611±432 grams and mean PMA of 32.9±2.4 weeks. Univariate analysis showed that chorioamnionitis, intubation, surfactant use, PDA, sepsis/NEC, anemia, apnea, GER and IVH were significantly associated with the time to NCPAP wean. On multivariate analysis, among neonates that were intubated, BW was the only significant factor (𝑃<0.001) that was inversely related to time to successful NCPAP wean. Amongst non-intubated neonates, along with BW (𝑃<0.01), chorioamnionitis (𝑃<0.01), anemia (𝑃<0.0001), and GER (𝑃<0.02) played a significant role in weaning from NCPAP. Conclusion. Neonates were weaned off NCPAP at mean weight of 1611±432 grams and mean PMA of 32.9±2.4 weeks. BW significantly affects weaning among intubated and non-intubated neonates, though in neonates who were never intubated chorioamnionitis, anemia and GER also significantly affected the duration on NCPAP.